Factors associated with physical growth status among children aged 12−59 months in the Japanese National Growth Survey on Preschool Children: A retrospective analysis - Chisa Shinsugi; Hidemi Takimoto (Maternal and Child Nutrition, 2024)
Abstract This study aimed to examine the factors associated with physical growth status among children aged 12−59 months in Japan. Data from the 2010 National Growth Survey on Preschool Children, a nationwide cross‐sectional survey, were used for this analysis (n = 4196). After adjustment for confounding factors, multiple logistic regression analyses showed that boys who were born small‐for‐gestational‐age were more likely to be underweight (adjusted odds ratio [aOR]: 12.55, 95% confidence interval [CI]: [6.76−23.3], p < 0.001), stunted (aOR: 5.78, 95% CI: [3.48−9.60], p < 0.001) and wasted (aOR: 7.02, 95% CI: [3.30−15.0], p < 0.001), while boys who were large‐for‐gestational‐age were less likely to be stunted (aOR: 0.26, 95% CI: [0.11−0.60], p < 0.01). Girls who were born small‐for‐gestational‐age were more likely to be underweight (aOR: 5.42, 95% CI: [2.73−10.7], p < 0.001), stunted (aOR: 4.04, 95% CI: [2.43−6.73], p < 0.001) and wasted (aOR: 6.27, 95% CI: [2.55−15.4], p < 0.001), while girls who were large‐for‐gestational age were more likely to be overweight (aOR: 5.90, 95% CI: [1.64−21.3], p < 0.001). Moreover, the following factors were associated with the physical growth status in children: maternal prepregnancy body mass index, complications during pregnancy, continuous breastfeeding, initiation age of complementary feeding, smoking status of the father or those living with the mother during pregnancy and birth order. Further research is needed to expand support for high‐risk families and to verify their effectiveness.